THE IMPORTANCE OF DEVELOPING YOUTHS THINKING IN ENGLISH CLASSES (Web of Teachers: Inderscience Research, 2023)
This article highlites comments and opinions on the development of a foreign language and the thinking of youths. How important it is for teenagers to develop thinking is reflected in this article. The development of thinking is more effectively carried out in English classes. At the same time, the development of thinking is considered as an important factor not only in intensifying the process of teaching a foreign language, but also in the professional growth of pupils.